2018
DOI: 10.1148/radiol.2017161845
|View full text |Cite
|
Sign up to set email alerts
|

Non–Small Cell Lung Cancer Radiogenomics Map Identifies Relationships between Molecular and Imaging Phenotypes with Prognostic Implications

Abstract: Purpose To create a radiogenomic map linking computed tomographic (CT) image features and gene expression profiles generated by RNA sequencing for patients with non-small cell lung cancer (NSCLC). Materials and Methods A cohort of 113 patients with NSCLC diagnosed between April 2008 and September 2014 who had preoperative CT data and tumor tissue available was studied. For each tumor, a thoracic radiologist recorded 87 semantic image features, selected to reflect radiologic characteristics of nodule shape, mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(121 citation statements)
references
References 35 publications
2
119
0
Order By: Relevance
“…Recent developments in machine learning (ML)-based medical image analysis such as Radiomics provide encouraging examples of molecular phenotyping from imaging data. For instance, the non-invasive genetic profiling of lung carcinoma has been recently demonstrated [6], and imaging biomarkers have recently been shown to outperform the risk metrics defined in the current WHO classification of gliomas [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in machine learning (ML)-based medical image analysis such as Radiomics provide encouraging examples of molecular phenotyping from imaging data. For instance, the non-invasive genetic profiling of lung carcinoma has been recently demonstrated [6], and imaging biomarkers have recently been shown to outperform the risk metrics defined in the current WHO classification of gliomas [7].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this hypothesis, we believe that, in the early stage, the damage to the pancreatic parenchyma is different between MAP and SAP (MSAP and SAP). Radiomics uncovers information hidden in conventional images, thus revealing a potential biological basis . In our study, the damage to the pancreatic parenchyma may be reflected by radiomics in the early stage, and further study of pancreatic microcirculatory disturbances is expected to decode these radiomics findings.…”
Section: Discussionmentioning
confidence: 99%
“…That research found that 10 meta-genes defined multiple molecular pathways, including the epidermal growth factor (EGF) pathway, and also found meta-genes associated with frosted glass opaque shadows, irregular nodules, and undefined knots on the margins. 41 Further, recent studies have found that colorectal cancer (CRC) is characterized by significant intratumorally genetic heterogeneity, which can be evaluated on medical images also. A high-throughput platform has been developed to obtain genomic and transcriptional group data to characterize cancer at the molecular level better.…”
Section: Combining Radiomics With Genomicsmentioning
confidence: 99%